Development E-Assessment Using Kahoot! in Learning Chemistry of Electrolyte And Non-Electrolyte Solution Materials for SMA/MA - Guspatni, Guspatni; Aulya, Mela Devi (FKIP-Universitas Riau, 2023)
This research aims to develop an e-assessment using Kahoot! Valid, reliable, also practical in learning the chemistry of electrolyte and non-electrolyte solution materials. The research subjects consisted of validators in their fields, subject teachers, and class XI students of SMA Negeri 13 Padang. This development research uses the Borg & Gall development model. The instrument in conducting this study used validation sheets and practicality questionnaires. The average result from the expert validation questionnaire was obtained at 0.91, meaning the product is valid and can be used. Analysis of question items received an average validity and reliability of questions of 0.50 and 0.88, respectively, indicating that the product is valid and reliable. The difficulty level is 20